2022
DOI: 10.1111/cpr.13378
|View full text |Cite
|
Sign up to set email alerts
|

ZNF281 drives hepatocyte senescence in alcoholic liver disease by reducing HK2‐stabilized PINK1/Parkin‐mediated mitophagy

Abstract: We investigated the role of zinc‐finger protein 281 (ZNF281), a novel molecule, in ethanol‐induced hepatocyte senescence and uncovered the potential mechanism. Real‐time PCR, Western blot, immunofluorescence staining, and enzyme‐linked immunosorbent assay were performed to explore the role of ZNF281 in hepatocyte senescence. ZNF281 expression was upregulated in both alcohol‐fed mice livers and ethanol‐treated hepatocytes. Silence of ZNF281 in hepatocytes using siRNA mitigated ethanol‐caused decrease in cell vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Our IF analysis revealed that PAR level was significantly increased in untreated aged mice but was exacerbated by chronic alcohol consumption in both young and aged mice ( Figure 4 A). In vitro assays have shown that senescence, a stress response that universally occurs within tissues under pathophysiological conditions, is stimulated in hepatocytes by ethanol, suggesting that it plays a key role in ALD [ 44 ]; moreover, in hepatocyte cultures exposed to ethanol the SA-β-gal activity, a widely used biomarker of cellular senescence, is increased [ 45 ]. Interestingly, our results showed that the activity of SA-β-gal was increased in untreated 18-month-old mice, but this increment was observed from 12 months on and potentiated in 18-month-old mice subjected to the ALD model ( Figure 4 B), indicating that chronic alcohol consumption exacerbated the appearance of senescent cells in the liver of aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our IF analysis revealed that PAR level was significantly increased in untreated aged mice but was exacerbated by chronic alcohol consumption in both young and aged mice ( Figure 4 A). In vitro assays have shown that senescence, a stress response that universally occurs within tissues under pathophysiological conditions, is stimulated in hepatocytes by ethanol, suggesting that it plays a key role in ALD [ 44 ]; moreover, in hepatocyte cultures exposed to ethanol the SA-β-gal activity, a widely used biomarker of cellular senescence, is increased [ 45 ]. Interestingly, our results showed that the activity of SA-β-gal was increased in untreated 18-month-old mice, but this increment was observed from 12 months on and potentiated in 18-month-old mice subjected to the ALD model ( Figure 4 B), indicating that chronic alcohol consumption exacerbated the appearance of senescent cells in the liver of aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results highlight that plasminogen activator inhibitor-1 and early growth response protein 1 are important regulators of lipopolysaccharide-induced cellular senescence and alcoholic hepatitis [ 53 ]. Another fascinating study showed that a novel factor, zinc‐finger protein 281, is a driver of hepatocyte senescence during ALD by reducing hexokinase II-stabilized PTEN-induced kinase 1/Parkin-mediated mitophagy [ 54 ]. Returning to lysosomes, chronic ethanol consumption disrupts hepatic biogenesis and inhibits the ubiquitin‒proteasome system by impeding hepatic proteasome activity [ 55 ].…”
Section: Common Molecular Eventsmentioning
confidence: 99%
“…Alcoholic liver disease (ALD) is a major cause of acute and chronic liver injury and can include simple steatosis, steatohepatitis, advanced fibrosis, cirrhosis, and even hepatocellular carcinoma [ 1 , 2 ]. ALD can be caused by byproducts or metabolites produced during alcohol metabolism and is a major factor that induces chronic liver disease [ 3 ].…”
Section: Introductionmentioning
confidence: 99%